Case study of training deans at a community college - Silveira, Michael (Kansas State University, 2021)
Community college deans and other mid-level academic leaders contribute to institutional processes on several levels and work with many constituencies. Studies have demonstrated that these leaders are expected to possess a wide array of attributes, but typically do not undergo formal training. The literature contains documentation of other levels of community college leadership but is deficient in information regarding dean development. Therefore, the purpose of this study was to investigate and document dean training in a community college that maintained training for mid-level academic leaders. This exploratory sequential case study examined dean training at a nationally recognized community college. Andragogy provided a theoretical lens for analysis and a conceptual lens was provided by the leadership competencies for mid-level academic leaders created by the American Association of Community Colleges. The first qualitive phase included semi-structured interviews with training program contributors and documents related to dean training were analyzed. Training program elements that emerged from interview data informed the development of the survey instrument used during the second phase of the study. Deans at the case study institution were surveyed to capture the perceived importance of including various competencies in a dean training program and value of different training methods. The findings of this study agreed with previous studies that indicated community college deans are expected to understand a wide array of topics. After interview data were consolidated, 68 training competencies and 30 methods emerged as dean training elements. Almost all competencies were perceived as important or somewhat important to include in a dean training program. Classifying competencies as informational, leadership, or procedural revealed that procedural competencies emerged more often, but leadership competencies were perceived as more important. Most training methods were perceived as valuable or somewhat valuable by deans at the institution. Practical applications of this study provide considerations for institutions and organizations interested in developing community college deans and other mid-level academic leaders.
Keywords: Community college; Dean; Professional development; Training